An Italian survey on the attitudes and beliefs of public health professionals towards mandatory vaccination: a pilot stud (Epidemiology, Biostatistics, and Public Health, 2023)
Background: This pilot study aimed to test a questionnaire developed to assess the attitudes and beliefs of Italian public health professionals towards mandatory vaccination for school-aged children.Methods: The online questionnaire was administered to members of the Italian Society of Hygiene, Preventive Medicine and Public Health. Internal consistency was measured using Cronbach’s alpha.Results: Fifty-two people answered the questionnaire: 90.4% were in favour of mandatory vaccination. Overall, the alpha score was above the cut-off value of 0.70.Conclusion: The questionnaire has proved a valid tool for assessing the attitudes and beliefs of Italian public health professionals towards mandatory vaccination.